Transcultural Poetics: Dissolving Borders in the Poetry of Li-Young Lee - Ezzeldin, Hend Hamed (European Journal of Multidisciplinary Studies, 2017)
:In a world characterized by a loss of direction, an absence of hope, and a disbelief in spirituality, a world that disrespects differences, obliterates human relations, and undermines emotions, man tends to lose faith in humanity. Amidst this debris of human fragmentation and disconnectedness, Li-Young Lee ventures to reach the whole world by transcending time and space, appealing to the metaphysical, and excluding the cultural. This research paper aims to highlight Li-Young Lee’s endeavors at creating tight bonds between himself and the rest of the world by unifying the dichotomies of the self and the other, interlacing a web of mutuality to embrace the entire universe. Lee calls into question the separation between beginning and end, birth and death, past and future, man and woman, and body and mind attempting to create a universal dialogue reflecting transcultural hybridity. To attain his goal, Lee depends on his memories to write poetry that is deeply personal but is universal in its appeal. Borders dissolve and language opens up to become the go-between the self and the other, giving meaning to what is invisible and evanescent.